1980
DOI: 10.1007/bf00025148
|View full text |Cite
|
Sign up to set email alerts
|

The effects of apple rootstock genotypes on mineral content of scion leaves

Abstract: M&s, apple rootstocks, leaf mineral content, components of variance. SUMMARYThe relative effects of year to year variation and rootstock genotypes on the major content of leaves of four apple scion cultivars were studied. For nitrogen and phosphorus the main source of variation was due to years. For potassium, magnesium and calcium there were significant genetic effects. The results are discussed in relation to breeding for improved efficiency in mineral uptake in apple rootstocks. Particular reference is made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 13 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…Starkspur Supreme Delicious was significantly different when grafted on the rootstocks M 7 EMLA, M 9, M 26 EMLA, and M 27 EMLA (Rom et al 1991). Kennedy et al (1980) reported that leaf N concentration was more influenced by environmental factors than by rootstock genotype. Leaf P concentration of scions on M 7 were lower than on MM 106, whereas leaf K concentration of scions on MM 109 and seedling were higher than those on MM 106 and M 7 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Starkspur Supreme Delicious was significantly different when grafted on the rootstocks M 7 EMLA, M 9, M 26 EMLA, and M 27 EMLA (Rom et al 1991). Kennedy et al (1980) reported that leaf N concentration was more influenced by environmental factors than by rootstock genotype. Leaf P concentration of scions on M 7 were lower than on MM 106, whereas leaf K concentration of scions on MM 109 and seedling were higher than those on MM 106 and M 7 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The higher concentration of leaf K in the trees on M.7 EMLA trees, as discussed earlier, is a good example for year-to-year variation of leaf minerals as a result of crop load changes. Several researchers have found yearto-year variation in the mineral compositions of apple leaves (Eaton and Robinson, 1977;Kennedy et al, 1980). Kennedy et al (1980) noted that year-to-year differences in leaf N and P concentrations were greater than the rootstock differences, whereas significant influences of rootstocks were seen for leaf K, Mg, and Ca.…”
Section: Experiments With Rootstocks For 'Fuji' At the University Of Imentioning
confidence: 99%
“…Several researchers have found yearto-year variation in the mineral compositions of apple leaves (Eaton and Robinson, 1977;Kennedy et al, 1980). Kennedy et al (1980) noted that year-to-year differences in leaf N and P concentrations were greater than the rootstock differences, whereas significant influences of rootstocks were seen for leaf K, Mg, and Ca. Whitfield (1963) suggested that fertilizer requirements vary due to season and rootstock.…”
Section: Experiments With Rootstocks For 'Fuji' At the University Of Imentioning
confidence: 99%
“…In many grafted cultivated species, the vegetative growth of the scion and the mineral nutrition are strongly affected by the rootstock; for example, the rootstock genotype influences the elemental composition of the scion in mandarin (Fallahi and Rodney ), apple (Kennedy et al. ) and oranges (Smith et al. ).…”
Section: Introductionmentioning
confidence: 99%